Fyysisen aktiivisuuden ja koetun työkyvyn välinen yhteys suomalaisväestössä sosioekonomisen aseman mukaan - Koskinen, Miia (2025)
Koskinen, M. 2025. Association between physical activity and perceived work ability by socioeconomic position in the Finnish population. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in physiotherapy, 69 pp. 1 appendix.